Farmers Perceptions On the Performance of Field Agricultural Extenders in Rempanga Village, Kutai District Kartanegara: Persepsi Petani Terhadap Kinerja Penyuluh Pertanian Lapangan di Desa Rempanga Kabupaten Kutai Kartanegara - Fahreza, Fiqri B; Sutadji, Sutadji; Abdullah, Zulkifli (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
ABSTRACT: This study describes and analyzes the Perceptions of Farmer Groups on the Performance of Field Agricultural Extension (PPL) in Rempanga Village, Loa Kulu District, Kutai Kartanegara Regency, and to identify whether farmers understand the main duties and functions of field agricultural extension agents in Rempanga Village, Loa Kulu District, Kutai Kartanegara Regency. The type of research used is descriptive qualitative. The research focus in this thesis refers to how farmers understand the performance of field agricultural extension agents (PPL) in the sustainability of the agricultural process. The data sources were obtained from primary data, namely conducting interviews with key informants and informants, and secondary data from the archives and documents of the Rempanga Village Office as well as other documents related to this research. The data analysis technique used is an interactive data analysis method. Based on the results of research in the field of Farmer Groups' Perceptions of Field Agricultural Extension (PPL) performance, it can be said that the absence of agricultural instructors has had a quite visible negative impact, especially in terms of assistance and education which is an obstacle to running agriculture in Rempanga Village. ABSTRAK: Penelitian ini mendeskripsikan dan menganalisis mengenai Persepsi Kelompok Tani Atas Kinerja Penyuluh Pertanian Lapangan (PPL) di Desa Rempanga Kecamatan Loa Kulu Kabupaten Kutai Kartanegara, dan untuk mengidentifikasi apakah para petani mengerti tugas dan fungsi utama penyuluh pertanian lapangan di Desa Rempanga Kecamatan Loa Kulu Kabupaten Kutai Kartanegara. Jenis penelitian yang digunakan adalah deskriptif kualitatif. Fokus penelitian dalam skripsi ini mengacu pada bagaimana petani memahami kinerja penyuluh pertanian lapangan (PPL) dalam keberlangsungan proses pertanian. Sumber data diperoleh dari data primer yaitu melakukan wawancara dengan key informan dan informan, dan data sekunder yang berasal dari arsip dan dokumen-dokumen Kantor Desa Rempanga maupun dokumen lain yang terkait dengan penelitian ini. Adapun teknik analisis data yang digunakan adalah metode analisis data interaktif. Berdasarkan hasil penelitian dilapangan Persepsi Kelompok Tani Atas Kinerja Penyuluh Pertanian Lapangan (PPL) dapat dikatakan bahwa ketiadaan penyuluh pertanian membawa dampak negatif yang cukup terlihat terutama dalam segi bantuan serta edukasi yang menjadi kendala jalannya pertanian di Desa Rempanga.